Underpricing of initial public offers in Malaysia - Syed Daniel B Syed Taha (2015)
Many studies have documented that underpricing of new issues takes place in almost all bourses. However, a review of studies by Dawson (1985), Dawson (1987), and Yong (1990) demonstrates that such a phenomenon provides the highest initial returns in Malaysia. This study examines the aftermarket performance of new issues in Malaysia from 1984 to 1992 and presents evidence for underpricing. The empirical results show that the initial underpricing, that is, the difference between the offer price and the opening price on the first trading day, is at an average of 81.06%. The average excess returns after the first day and up to a period of one month are negative. However, our findings show that a positive excess return is generated after one year of trading on the Kuala Lumpur Stock Exchange (KLSE). This study, in testing the relationship between the degree of underpricing and certain issue-related characteristics, finds that Initial Public Offers are always highly . underpriced whenever the issues are heavily oversubscribed or whenever such issues are to be listed on the Main Board of the KLSE.